2019
DOI: 10.1016/j.resuscitation.2018.09.026
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the ability of the National Early Warning Score and the National Early Warning Score 2 to identify patients at risk of in-hospital mortality: A multi-centre database study

Abstract: Aims: To compare the ability of the National Early Warning Score (NEWS) and the National Early Warning Score 2 (NEWS2) to identify patients at risk of in-hospital mortality and other adverse outcomes. Methods:We undertook a multi-centre retrospective observational study at five acute hospitals from two UK NHS Trusts. Data were obtained from completed adult admissions who were not fit enough to be discharged alive on the day of admission. Diagnostic coding and oxygen prescriptions were used to identify patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
106
3
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(124 citation statements)
references
References 29 publications
12
106
3
3
Order By: Relevance
“…By means of logical, rank and consistency tests, the database was cleaned resulting in a total of 32 variables. Then a full analysis was carried out, variable-by-variable of unknown data, only considered for the analysis of vital signs, in line with previous studies [27,28]. The study variables do not present lost data.…”
Section: Missing Datamentioning
confidence: 97%
See 1 more Smart Citation
“…By means of logical, rank and consistency tests, the database was cleaned resulting in a total of 32 variables. Then a full analysis was carried out, variable-by-variable of unknown data, only considered for the analysis of vital signs, in line with previous studies [27,28]. The study variables do not present lost data.…”
Section: Missing Datamentioning
confidence: 97%
“…The regular assessment of the risk of deterioration through EWS is a standard procedure in multiple clinical context the use of which is more than contrasted [14,15,28] and which can help to detect patients with TBI and a high risk [49,50]. Determining which patients may be subsidiaries of advanced procedures and rapid transportation to a useful center must be a priority for the EMS [51].…”
Section: Early Warning Scores (Ews) and Prehospital Tbimentioning
confidence: 99%
“…Indeed, some research has used different thresholds to differentiate patients with respiratory conditions (CREW: Lobo, Lynch, & Casserly, ), while others suggest developing different algorithms for groups with distinct physiological profiles (Downey et al, ). However, an increasing body of research has found EWS (particularly NEWS) may be suitable for diverse patient groups, including those with COPD (Hodgson, Congleton, Venn, Forni, & Roderick, ; Hydes et al, ; Kovacs et al, ; Pimentel et al, ; Redfern et al, ). Interviewees also disputed the necessity of the frequency of observations overall and whether there was always a need to take a whole set of observations, which reflects gaps in the evidence base (Smith et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Such a theory needs rigorous testing and without establishing the evidence base for adding confusion/delirium and that NEWS2 has increased sensitivity, specificity and positive predictive values than NEWS, we may be at risk of inadvertently undermining the efficiency of our escalation systems rather than improving them. 9,17 So, like other researchers, we also call for a more careful evaluation of NEWS2, with smaller scale testing, before widespread, financially incentivised, implementation. 11,17 It is, however, important to note that our findings should not detract from the importance and seriousness of confusion or delirium, especially in elderly hospitalised patients.…”
Section: Policy Implicationsmentioning
confidence: 92%
“…9,17 So, like other researchers, we also call for a more careful evaluation of NEWS2, with smaller scale testing, before widespread, financially incentivised, implementation. 11,17 It is, however, important to note that our findings should not detract from the importance and seriousness of confusion or delirium, especially in elderly hospitalised patients. 18,19 Nevertheless, with a relatively high prevalence of confusion or delirium amongst the hospital population, the proposed implementation of NEWS2 could swamp clinical staff with alerts that yield lower 'signal to noise' ratios than NEWS because a higher NEWS2 may no longer be as indicative of acute deterioration in physiological response to illness as NEWS.…”
Section: Policy Implicationsmentioning
confidence: 92%